Evaluasi Pengawasan Bawaslu Kota Jambi terhadap Pemutakhiran Data Pemilih Berkelanjutan Tahun 2025 - Naibaho, Yola Agnesia; Nasuhaidi, Nasuhaidi; Ahmad, Zakly Hanafi (Indo Publishing, 2026)
Continuous Voter Data Updating (PDPB) is a policy designed to maintain the accuracy and integrity of voter lists on a regular basis outside the electoral stages. This study aims to analyze the implementation of the 2025 Continuous Voter Data Updating in Jambi City and to evaluate the supervision carried out by the Jambi City Election Supervisory Agency (Bawaslu) in ensuring the quality of the voter list. This study used a qualitative approach with a descriptive method. The data were collected through in-depth interviews with commissioners and staff of Bawaslu Jambi City, officials of the Jambi City General Election Commission (KPU), and other relevant stakeholders, supported by documentation studies of laws and regulations, supervisory reports, and other electoral documents. The data were analyzed using the interactive model of Miles and Huberman, which consisted of data reduction, data display, and conclusion drawing, while data validity was ensured through source and method triangulation. The results show that the implementation of the 2025 PDPB in Jambi City has procedurally been carried out regularly and in accordance with existing regulations, but substantively it has not been fully optimal. There are still inconsistencies in voter data caused by delays in updating death records, changes of domicile, the lack of optimal data integration among institutions, and low public participation in reporting data changes. Bawaslu Jambi City has performed preventive and corrective supervisory functions through data examination, field spot checks, the provision of corrective recommendations, and the receipt of public reports. Such supervision has contributed to improving the accuracy and accountability of the voter data updating process, although its effectiveness remains limited because Bawaslu’s authority is recommendatory in nature and the follow-up actions largely depend on coordination with the KPU and other related institutions. Therefore, strengthening data integration, institutional coordination, and public participation is necessary to ensure the sustained quality of the voter list.